Frequency of Back Pain in Knee Osteoarthritis Patients; A Cross Sectional Study: Frequency of Back Pain in Knee Osteoarthritis Patients - Fida, Nisha; Batool, Sana; Javaid, Maham; Ahmad, Ashfaq (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
Osteoarthritis is one of the major prevalent types of arthritis and knee joint is mostly involved site in geriatric patients in which half of the old patients with ages more than 50 years. It was found that these management strategies were effective in the reduction of pain and disturbance of the function induced by chronic low back pain and osteoarthritis. Therefore, the current study seeks to analyze the frequency of backache mainly in the region of low back is associated with the patients having knee osteoarthritis. Objective: To analyze and investigate the relationship amid back pain and knee osteoarthritis (OA) in order to check frequency of backache in knee osteoarthritis patients. Methods: A self-made questionnaires were distributed among the random population of 500 individuals and categorized them according to age, gender, occupation, body mass index, residence, back pain history, severity of pain and pain persistence. SPSS was used to analyze the results. Results: In this cross-sectional study, Back pain was associated significantly with knee osteoarthritis patients such as 310 (62%) individuals claimed to have backache with knee osteoarthritis (OA) as well. Obesity was also related with backache with 219 individuals suffer from backpain from 281 members. 67 patients had severe pain, 77 patients had mild pain and 150 patients experienced moderate pain. Conclusion: Back pain was found more prevalent (62%) from total collected individuals suffering from knee osteoarthritis